Safety of Skin-to-Skin Contact with Umbilical Venous Catheter in Preterm Infants: A Prospective Study - Montaner-Ramon, Alicia; Carrillo-Messa, Elena; Merayo-Fernandez, Laura; Cosmo-Garcia, Inmaculada; Ramos-Soriano, Isabel; Gonzalez-Garcia, Laura; Camba-Longueira, Fatima (American Journal of Perinatology, 2024)
Objective For many health care providers, an umbilical venous catheter (UVC) may be a contraindication for skin-to-skin contact (SSC). Our aim was to compare the frequency of adverse events between preterm infants who were on SSC with UVC and those who remained in an incubator.Study Design Prospective observational study in newborns less than 35 weeks gestation. UVC-related adverse events were compared between neonates who performed SSC and those who did not. The incidence of catheter-related displacement, leak, loss, hemorrhage, malfunction, and bloodstream infection was studied.Results From 226 patients, 171 performed SSC with UVC. Their first contact was earlier than in those who remained in an incubator (SSC-UVC, 29 hours [interquartile range (IQR): 21–53] vs. no SSC-UVC, 132 hours [IQR: 96–188]; p < 0.001). Both groups were similar in gestational age (SSC-UVC, 30 weeks vs. no SSC-UVC, 30.3 weeks; p = 0.331) and birth weight (SSC-UVC, 1,285 g vs. no SSC-UVC, 1,355 g; p = 0.2). Studied complications were not more frequent in patients who performed SSC. In fact, although it was not statistically significant, a lower overall incidence of adverse events (SSC-UVC, 13.5% vs. no SSC-UVC, 20%; p = 0.237) and catheter-related bloodstream infection (SSC-UVC, 4.7% vs. no SSC-UVC, 10.9%; p = 0.111) was observed in this group.Conclusion SSC with a UVC is a safe procedure and there are no more complications in newborns who perform SSC compared to those who remain in the incubator. Due to its demonstrated benefits, SSC should be promoted in premature newborns regardless of the presence of a UVC.Key Points
Keywords: prematurity; skin-to-skin contact; umbilical catheter; neonatal intensive care; NIDCAP